Phenotype and carcass characteristics of Shugor sheep in Rahad Scheme, Sudan - E. Elimam, Mohmed; F. F. Babikir, Mohmed (Gezira Journal of Agricultural Science; Vol 10 No 1 (2012), 2023)
Two experiments were conducted to study the phenotype and carcass characteristics of Shugor sheep which is an important meat producer in Rahad Scheme, Sudan. In experiment 1, phenotypic traits including body weight (BW), height at withers (HW), heart girth (HG), abdominal girth (AG), body length (BL), tail length (TL) and ears length (EL) were measured  in 200 ewes at 1- 4 year old. Mean BW and phenotypic traits generally increased with age. Mean BW was 24.1 – 45.0 kg and mean HW, HG, AG, BL, TL and EL (cm) were, 69.58 – 79.72, 75.48 – 90.94, 90.23 – 110.34, 60.08- 66.72, 58.54 – 66.34 and 17.94 – 22.31, respectively. All animals were polled. There were significant (P < 0.05) correlations between BW and phenotypic traits. Different regression equations were used to predict BW from AG, HW and BL at different ages with no significant differences (P≥ 0.05) between actual (measured) and predicted BW. In experiment 2, eight Shugor sheep males were bought from Elfao livestock market at 6 months or 1 year old (4 in each group) and slaughtered to study body components and carcass characteristics. Body components percentages on empty body weight (EBW) basis decreased with increasing the slaughter age, except the kidneys, and the decrease was significant (P < 0.05) for the legs and the heart. Slaughter weight, EBW, hot carcass weight, total carcass muscles, bones, fat, muscle: bone and muscle: fat ratios significantly differed (P < 0.05) with slaughter age. Dressing percentages expressed on LBW and EBW basis were not significantly affected by slaughter age. Slaughter age had no significant effects on whole sale cuts percentages, except the leg and chump.